Evaluacion de un secador de capa fija acoplado a un colector solar plano - Best, R.; Alonso, L. (International Center for Tropical Agriculture, 1984)
The components and operation of a fixed layer cassava dryer coupled to a flat solar collector are described, and the results obtained when using this dryer in cassava drying trials are presented. The dryer operates from 07:00 to 19:00 h, with a flow of 106 cubic meters/min. The solar collector increases the av. air temp. from 30.7 to 35.7 degrees Celsius, thus lowering the RH from 61.8 to 46.0 percent. The load for the dryer is estimated to be 150 kg/square meter during an av. 24-h period. Based on the results obtained, it was estimated that to establish a combined natural/artificial drying system, a drying floor area of 200 square meters requires a fixed layer dryer of 6 square meters. Investment and operating costs are presented. (CIAT)